Keaktifan Belajar Ditinjau Dari Penggunaan Media TIK Dan Internet (Studi Kasus Mata Kuliah Media Pembelajaran Berbasis TIK) Pada Mahasiswa Pendidikan Akuntansi FKIP UMSTAHUN AJARAN 2015/2016 - Permatasari, Okadita, Drs. Djoko Srijono, M.Hum (2016)
The objetives of this research are to know: 1) the use of ICT media toward students' learning activeness in ICT based Learning Media subject. 2) the use of internet toward students' learning activeness in ICT based Learning Media subject. 3) the use of ICT media and internet toward students' learning activeness in ICT based Learning Media subject. This research employs quantitative associative method. The population in this research are the students of Department of Accounting Education 2015/2016 academic yearwho take ICT based Learning Media subject as many as 181 students. The sampling technique used is Random Sampling as many as 119 respondents. The data needed are acquired through questionnaire which has been tested with validity and reability test. The data analysis technique used in this research is double regression linear test, t test, F test, R2 test and relative and effective contribution. The result of regression test are acquired regression equation: Y= 34,772 + 0,25X1 + 0,381X2. The conclusion of this research are: 1) The use of ICT media has significant effect toward learning activeness of ICT based Learning Media of Department of Accounting Education's students FKIP Muhammadiyah University of Surakarta 2015/2016 academic year. Based on t test are acquired thitung> ttabel that is 3,239 > 1,981 (α=5%) and significancy score < 0,05 that is 0,000. 2) The use of internet has significant effect toward learning activeness of ICT based Learning Media of Department of Accounting Education's students FKIP Muhammadiyah University of Surakarta 2015/2016 academic year. Based on t test are acquired thitung> ttabel that is 4,642 > 1,981 (α=5%) and significancy score < 0,05 that is 0,000. 3) The use of ICT media and Internet has significant effect toward learning activeness of ICT based Learning Media of Department of Accounting Education's students FKIP Muhammadiyah University of Surakarta 2015/2016 academic year. Based on F test are acquired Fhitung> Ftabel that is 34,032 > 3,074 significancy rate 5%. X1 variable gives relative contribution as much as 38,6% and effective contribution as much as 14,3%, X2 variable gives relative contribution as much as 61,4% and effective contribution as much as 22,7%.